Adsorption of amphiphilic grafted polymers as polymer corrosion inhibitors: insights from mesoscopic simulations. Issue 19 (9th May 2022) - Díaz, Javier; Soltau, Marko; Lísal, Martin; Carbone, Paola; Pagonabarraga, Ignacio
Abstract : Dissipative particle dynamics are used to study the conformation and adsorption behaviour of amphiphilic grafted polymers at surfaces. Various morphologies are identified depending on the chemical interactions, grafting density and concentration. Abstract : The homogeneous covering of amphiphillic polymer molecules onto metallic surfaces is of great importance for corrosion inhibitor applications. Lyophillic side chains grafted onto a lyophobic backbone act as anchors that allow the molecule to absorb at the metallic surface preventing the exposure with the solvent. Coarse-grained simulations are used to study the sorption and conformation behaviour of amphiphillic grafted polymers for corrosion inhibition. The backbone insolubility is found to play a key role in the sorption and conformation behaviour in the dilute limit. For finite concentrations, moderate backbone solubility and moderate molecule concentrations achieve optimal surface coverage, while highly a lyophobic backbone leads to bulk-like structures as a consequence of aggregation.